CHROMATOGRAPHIC METHOD OF SEPARATION OF RADIONUCLIDE LUTETIUM-177, CARRIER FREE FROM MACRO-QUANTITIES OF YTTERBIUM - Akhmedov Zh. A; Usarov Z. O; Abdukayumov A. M; Rikhsiev A. Z; Sherov O. O (International Engineering Journal For Research & Development, 2021)
Currently, promising direction of development of modern oncology is a radionuclide therapy using radiopharmaceuticals sighting direction, ie the targeted effect on tumor tissue. For this purpose, suitable radionuclide 177Lu, possessing optimal nuclear-physical characteristics with an average half-life (T1/2 = 6,7 days); acceptable energy β-particles (maximum 0,5 MeV), which allows to destroy small tumors and metastasis without affecting the healthy tissues; concomitant soft γ-radiation with sufficient energy for imaging. Targeted exposure helps to get rid of neuroendocrine tumors, thyroid cancers, some types of brain cancer, and prostate cancer, and so on.